2004
DOI: 10.1016/j.jad.2003.12.008
|View full text |Cite
|
Sign up to set email alerts
|

A population study of the association between sexual function, sexual satisfaction and depressive symptoms in men

Abstract: The findings suggest that depressive symptoms are linked to ED by the mediation of decreased sexual activity and the dissatisfaction generated by the inability to have a healthy sexual life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
102
0
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(123 citation statements)
references
References 35 publications
15
102
0
6
Order By: Relevance
“…The prevalence of moderate or complete ED (IIEF score p16) has been reported 78% among Saudi patients with diabetes, 23 73% in the current study, 66% among Japanese patients 24 and 64% among Chinese men with diabetes. 25 Our findings consistent with previous studies 1,2,9,10,13,23 showed that ED is associated with age, duration of diabetes, CVD, depression and poor metabolic control. ED is often related to the severity and duration of diabetes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The prevalence of moderate or complete ED (IIEF score p16) has been reported 78% among Saudi patients with diabetes, 23 73% in the current study, 66% among Japanese patients 24 and 64% among Chinese men with diabetes. 25 Our findings consistent with previous studies 1,2,9,10,13,23 showed that ED is associated with age, duration of diabetes, CVD, depression and poor metabolic control. ED is often related to the severity and duration of diabetes.…”
Section: Discussionsupporting
confidence: 91%
“…8 There is also a bidirectional relationship between depression and ED. 9,10 Depressive symptoms cause ED, and depression is a consequence of ED. Both conditions have a negative effect on the quality of life of patients and their partners.…”
Section: Introductionmentioning
confidence: 99%
“…Comorbidity between male erectile dysfunction and depression is known to be high but the nature of the relationship between the two conditions is unclear. 26,27 Although the distress of erectile dysfunction may contribute to the development of depression, it is also possible that depressive illness may lead to erectile difficulties. There have been data from a prospective study suggesting that the incidence of erectile dysfunction is increased among men with depression.…”
Section: Discussionmentioning
confidence: 99%
“…Patients presenting with ED should be screened for depression while patients with depression will need to be screeened for ED (Araujo et al, 1998). One study by Nicolosi et al, 2004, found a relationship between ED, depression, sexual activity and sexual satisfaction.…”
Section: Depressionmentioning
confidence: 99%